About the media «fighting arena» around the indigenous populations in Argentina: An interdisciplinary approach to information frames - Lencina, Rocio (2023)
In this work we propose to analyze the journalistic coverage around the indigenous peoples of Argentina in 15 digital national information portals. In this framework, we developed an exploratory-descriptive methodological strategy that contemplated: survey of cases, systematization, analysis, and interpretation of informative productions on indigenous peoples published between January, February, and March 2021. As a result, we observed a great invisibility of the agendas and realities of these groups, and the preponderance of the conflict frame in news constructions.